Recovery of Orchids in the Post Gold Mining Landscape of Combretum-Terminalia Woodland Ecosystem (Indian Journal of Advanced Botany (IJAB), 2025)
Benishangul Gumuz Region stands out for its remarkable endemism and diversity of orchids, in which 63 different orchid species have been recorded so far. However, this wealth of diversity is potentially at risk due to habitat loss caused by the newly booming mineral mining industry and other regional developments. Consequently, species extinction is occurring at an alarming rate, one year shorter than projected. Therefore, it is necessary to periodically assess the status of orchid diversity to determine the extent of the threat and devise the appropriate conservation measures. To address this issue, the researcher utilised preserved forests bordering abandoned postmineral exploitation areas as a model to determine the status of orchids through systematic field surveys conducted over four years (2021-2024). For the Orchids survey purpose, a total of 90 quadrant sample plots, each 10 x 10 m in size and spaced at an interval of 50 meters along six parallel transects, were established. The survey result revealed that of the previous 63 orchid species known, only 42 were found, of which only 20 were recorded in post-mining sites. There was a significant difference (P < 0.05) between the orchid species diversity at all sites surveyed, except for the diversity comparison between the mining site abandoned for five and ten years (P > 0.05). Moreover, the orchid diversity of the region was depicted as medium (H' = 3.969) for the unmined area and low (H' = 2.73) for post-mining sites. According to the data on summed dominance ratio (SDR), Nervilia simplex (SDR = 4.10), Habenaria aethiopica (SDR = 5.88), and Bulbophyllum scaberulum (SDR = 9.47) were the top three dominant species in the post-gold mining sites and were considered disturbance opportunists. Concerning elevation parameters, the total number of orchid species follows a unimodal pattern with elevation. The highest species number (127 individuals) was observed at elevations of 861–925 meters and 926–1153 meters, while the lowest species number (72 individuals) was found at elevations below 860 meters. In this study, the number of orchid species was significantly lower than the number in the initial research conducted at the exact location, and we were unable to find most of the previously described endemic orchids. This may be due to difficulty in establishing themselves even in the oldest abandoned gold mining sites as a result of Sevier degradation. Based on the study results, we recommend establishing an effective regulatory mechanism to ensure the proper rehabilitation of gold mining sites through appropriate biological treatments before investors abandon leased project sites.